Glucose breath test and Crohn's disease: Diagnosis of small intestinal bacterial overgrowth and evaluation of therapeutic response. (November 2015) - Greco, Anna; Caviglia, Gian Paolo; Brignolo, Paola; Ribaldone, Davide Giuseppe; Reggiani, Stefania; Sguazzini, Carlo; Smedile, Antonina; Pellicano, Rinaldo; Resegotti, Andrea; Astegiano, Marco; Bresso, Francesca
Abstract Objective. Small intestinal bacterial overgrowth (SIBO) is characterized by an abnormal proliferation of bacterial species in the small bowel. It has been shown that patients with Crohn's disease (CD) have a higher risk of SIBO development. The aim of the present study was to investigate SIBO prevalence in CD patients, possible clinical predictors of SIBO development and response to antibiotic therapy. Material and methods. Sixty-eight patients (42 male, 26 female; mean age 49.3 ± 12.8 years) with CD reporting abdominal complaints were prospectively evaluated for SIBO with H2/CH4 glucose breath test (GBT). Results. Of the 68 patients enrolled, 18 (26.5%) tested positive for SIBO. Patients with SIBO exhibited increased stool frequency and significant reduction of stool solidity (p = 0.014), were older than patients tested negative to GBT (54.3 ± 13.0 years vs. 47.5 ± 12.3 years, p = 0.049), reported a longer history of CD (21.2 ± 10.3 years vs. 15.7 ± 10.2 years, p = 0.031) and showed a significant higher frequency of prior surgery (p = 0.001), revealing an association of number of surgical procedures (OR = 2.8315, 95% CI = 1.1525–6.9569, p = 0.023) with SIBO. Breath test normalization occurred in 13/15 patients evaluated after antibiotic and probiotic therapy. Although vitamin B12 levels were lower in patients with SIBO (p = 0.045) and a significant improvement was found after treatment (p = 0.011), this could be due to the heterogeneity, regarding vitamin B12 treatment, in our cohort. Conclusion. SIBO is a frequent but underestimated condition in CD, which often mimics acute flare, effectively identified with GBT and could be treated with a combined antibiotic and probiotic therapy.